FUZZY BASED PREDICTION OF ANGULAR DISTORTION OF GASMETAL ARC WELDED STRUCTURAL STEEL PLATES - Lohate M.S; Dr. Damale A.V (International Journal of Innovations in Engineering Research and Technology, 2021)
Angular Distortion is a major problem and most discussed among the different types of distortion occurring in the welded joints. The main cause of angular distortion is non-uniform transverse shrinkage along the depth of welded plates. The angular distortion restriction may leads to high residual stresses, but can be reduced by providing initial angular distortion in negative direction. So for this the value i:e magnitude of angular distortion must be known. It is difficult to obtain a complete analytical solution to predict the angular distortion. In this paper the process parameters affecting the angular distortion are studied. The Fuzzy Logic is used for the prediction of angular distortion with the multipass Gas Metal Arc Welding (GMAW) process parameters. The effects of parameters were represented graphically and compared with the experimental results from thereferences. It was found that the results obtained from Fuzzy logic tool and by experimentation in references, have good agreement between them.